Revitalization and Development of Cultural Heritage Tourism in Gresik Old City - Nuruddin, Nuruddin (Institut Pariwisata dan Bisnis Internasional, 2023)
Together with old cities in Southeast Asia, Gresik is a city visited by many world traders in the 15th century. Some of the old cities have been transformed into tourist areas, while those in Gresik have not yet been realized. This study aims to analyze the government's efforts to revitalize cultural heritage and its use as a tourist attraction in the old town of Gresik. This study uses a qualitative method with a critical descriptive approach with interpretive analysis. Research data were obtained from government archives, library sources in the form of books and scientific articles, interviews with stakeholders in the Gresik old town area. After the data is collected, the research is continued with the process of data analysis using a qualitative interpretive analysis approach. The results of this study can be concluded that activities related to preservation, revitalization and utilization of cultural heritage in the old city of Gresik have not been maximized. This can be seen from the efforts to identify and determine cultural heritage that have not been completed; spatial planning of cities in historical areas still leaves many differences of opinion; and regulations regarding tourism planning in the old city of Gresik do not yet exist. The solution that can be done is to involve the community who owns ancient buildings from data collection to tourism management, so that the tourism that is developed can be sustainable.